Collective construction experience in extension practices: addressing the problem of micro-trash dumps and zoonotic diseases in Casilda, Santa Fe (Cuadernos de Extensión Universitaria de la UNLPam, 2024)
In this article we will present the experience of an Extension Project developed in the Nueva Roma C and D neighborhood of the city of Casilda. This lasted three years and was structured in two stages, which had the objective of knowing, analyzing and intervening in the environmental problems faced by people who live in the neighborhood, linked to their companion animals. To carry out this analysis, an interdisciplinary and inter-institutional group was formed. The result of this work is reflected in various prevention and health promotion strategies specifically aimed at residents of the neighborhood, and a joint call with the neighborhood's social organizations to the municipal authorities to urgently address the urbanization of the area.
Keywords: zoonotic diseases; university extension; environment; micro-trash dumps; health prevention